MRI Findings of Early-Stage Hyperacute Hemorrhage Causing Extramedullary Compression of the Cervical Spinal Cord in a Dog with Suspected Steroid-Responsive Meningitis-Arteritis - Wang-Leandro, Adriano; Huenerfauth, Enrice-Ina; Heissl, Katharina; Tipold, Andrea (Frontiers in Veterinary Science, 2017)
A 9-month-old female Weimaraner was presented to the emergency service due to episodes of fever and neck pain. Physical examination revealed a stiff neck posture and elevated body temperature. Shortly after clinical examination was performed, the dog developed peracute onset of non-ambulatory tetraparesis compatible with a C1-C5 spinal cord (SC) lesion. Immediately thereafter (<1h), MRI of the cervical SC was performed with a 3 Tesla scanner. A left ventrolateral intradural-extramedullary SC compression caused by a round-shaped structure at the level of C3-C4 was evidenced. The structure was iso- to slightly hyperintense in T1-weighted (T1W) sequences compared to SC parenchyma and hyperintense in T2-weighted, gradient-echo (GRE) and fluid-attenuated inversion recovery. Moreover, the structure showed a strong homogeneous contrast uptake in T1W sequences. Cerebrospinal fluid (CSF) analysis revealed a mixed pleocytosis, as well as elevated protein and erythrocyte count. Early-stage hyperacute extramedullary hemorrhage was suspected due to immune mediated vasculitis. The dog was maintained under general anesthesia and artificial ventilation for 24 hours and long-term therapy with corticosteroids and physiotherapy was initiated. Eight weeks after initial presentation, the dog was ambulatory, slightly tetraparetic. Follow-up MRI showed a regression of the round-shaped structure and pleocytosis was not evident in CSF analysis. This report describes an early-stage hyperacute extramedullary hemorrhage, a condition rarely recorded in dogs even in experimental settings.